POLITENESS STRATEGY BY ELLEN DEGENERES IN ELLEN SHOW WITH SENATOR HILLARY CLINTON AND THE PRESIDENT OF THE UNITED STATES MR. BARRACK OBAMA - Maria Skolastika; Yusniaty Galingging (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2019)
Politeness is used in many aspects of communication including mass media. This writing is focused on the pragmatic politeness of an interview on "The Ellen Show" tv talk show, between Ellen, the host, and her guests. According to www.broadwayworld.com, "The Ellen Show" is the best tv talk show in America. Because of it, the writer chooses "The Ellen Show" as the data source. The data in this research are positive and negative politeness strategies which are found in the transcripts of two episodes of "The Ellen Show". This is descriptive research. The theory that is used in this study is Brown and Levinson's politeness strategies. The writer analyzes what kind of positive and negative politeness Ellen used in interviewing her guests and why Ellen used those strategies. From this research, the writer finds that Ellen more uses positive politeness strategies and Ellen uses those strategies because of three reasons. First, she wants to avoid her guests' acts that might threaten her face. Second, Ellen wants to be approved by the guests so she can be intimate with them and their conversation can be interesting. Third, both of her guests are politicians that also compete in the American election. Ellen tries to be neutral and she does not want to be unimpeded. The writer suggests that students who want to analyze politeness strategies use more data and analyze other politeness strategies, so the readers can see clearly whether the object was polite or not, the research will be deeper, and the reader will be easier to understand politeness strategies.